1995
DOI: 10.1074/jbc.270.1.418
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the Promoter of the Human α1(XI) Collagen Gene

Abstract: In order to eventually elucidate the mechanisms regulating alpha 1(XI) collagen expression in cartilaginous and non-cartilaginous tissues, we performed an initial analysis of the structural-functional features of the promoter of the human gene (COL11A1). After cloning and sequencing the 5' portion of COL11A1, primer extension and nuclease protection assays identified several minor transcriptional start sites clustered around a major one located 318 base pairs from the ATG codon. Consistent with this finding, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 36 publications
0
45
0
1
Order By: Relevance
“…Culture-Human rhabdomyosarcoma cell line A204 (17,18) was used in this study. Cells were cultured in Dulbecco's modified Eagle's medium supplemented with 10% heart-inactivated fetal bovine serum (Sanko Junyaku, Tokyo) at 37°C in humidified 5% CO 2 /95% air.…”
Section: Cells and Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture-Human rhabdomyosarcoma cell line A204 (17,18) was used in this study. Cells were cultured in Dulbecco's modified Eagle's medium supplemented with 10% heart-inactivated fetal bovine serum (Sanko Junyaku, Tokyo) at 37°C in humidified 5% CO 2 /95% air.…”
Section: Cells and Cellmentioning
confidence: 99%
“…It was expressed in mesenchymal cells, and its level of binding activity was positively correlated with the degree of cell differentiation in osteoblastic and skeletal muscle cell lines, in vitro. At Ϫ395 to Ϫ379, the core sequence of FP7 exhibits some homology with that of FPB 1 in COL5A2, and FP7-protein complexes can be competed with an excess of FPB oligonucleotides in an EMSA using nuclear extracts from the 1120 cell line (17,19). Further studies using transfection experiments and EMSAs in A204 cells, however, indicated that the FPB-protein complexes identified were PBX, PREP and HOX proteins and therefore different from the FP7-binding proteins (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This renders the 5Ј-flanking region of COL15A1 similar to promoters of the "housekeeping genes," which are transcribed widely but at low RNA levels in many tissues. Several other collagen genes also contain multiple GC boxes as their main promoter elements, including the COL5A1, COL7A1, COL11A1, and COL11A2 genes (26,(32)(33)(34). In addition, the downstream promoter of COL6A2 (35) and the upstream promoter of Col18a1 (14), two collagen genes with alternate promoters, are also of this kind.…”
Section: Intron Boundaries Of the Gene Coding For The Human ␣1(xv) Comentioning
confidence: 99%
“…COL11A is expressed mainly in articular cartilage and controls collagen type II (9,10). It functions in skeletal morphogenesis, fibrillogenesis, chondrocyte maturation and bone mineralization (11,12).…”
Section: Introductionmentioning
confidence: 99%